2007
DOI: 10.1007/s11121-007-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Change in a Cognitive Behavioral Couples Prevention Program: Does Being Naughty or Nice Matter?

Abstract: Although there is a body of evidence suggesting beneficial effects of premarital prevention, little research directly examines the mechanisms of effect. One study that examined changes in communication following training in the Prevention and Relationship Enhancement Program (PREP) found that, although couples made the expected communication gains pre to post PREP, female gains in positive communication were paradoxically associated with worse, not better, outcomes (Schilling et al., J. Fam. Psychol. 17(1):41-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Nevertheless, there is not much evidence in this sample for relationship quality impacts that would appear sufficiently powerful to explain the divorce reduction effect, raising the possibility that other mechanisms produced the impact on divorce, such as non-specific or unmeasured effects (see Hawkins, Stanley, Blanchard, & Albright, 2012). Such issues pertain to the general question of mechanisms of impact, which, as others have noted, are important to elucidate (e.g., Wadsworth & Markman, 2011) but difficult to demonstrate (e.g., Schilling, Baucom, Burnett, Allen, & Ragland, 2003; Stanley, Rhoades, Olmos-Gallo, & Markman, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is not much evidence in this sample for relationship quality impacts that would appear sufficiently powerful to explain the divorce reduction effect, raising the possibility that other mechanisms produced the impact on divorce, such as non-specific or unmeasured effects (see Hawkins, Stanley, Blanchard, & Albright, 2012). Such issues pertain to the general question of mechanisms of impact, which, as others have noted, are important to elucidate (e.g., Wadsworth & Markman, 2011) but difficult to demonstrate (e.g., Schilling, Baucom, Burnett, Allen, & Ragland, 2003; Stanley, Rhoades, Olmos-Gallo, & Markman, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Stanley, Rhoades, Olmos-Gallo, and Markman (2007) attempted to replicate the Schilling et al paradoxical finding and could not do so in two independent samples. Stanley and colleagues argued that one potential explanation for the Schilling findings was that they analyzed partner scores together in their analyses and that such dependencies influenced the outcomes.…”
Section: General Perspectives On Mechanisms Of Changementioning
confidence: 97%
“…Stanley et al (2007) note that analyses of change are very complicated when it comes to couple level variables. As these authors point out, there is no clear consensus on how to handle such data and issues such as multicollinearity can affect findings including producing counterintuitive findings such as may be the case in Schilling et al A critical question raised by these authors is “when do couples levels of analyses poorly represent what is actually happening with couples (p. 236)….what does it mean to examine changes in female positivity if the change in her partner’s communication is controlled for (p. 237)?” Space precludes further discussion of these very important statistical issues (and of course there are other important issues as well when it comes to handling dyadic data over time) and readers are referred to Stanley et al (2007) for a fuller discussion of some of these issues.…”
Section: General Perspectives On Mechanisms Of Changementioning
confidence: 99%
“…While the latter results concerning positive communication in women are surprising and counterintuitive, Schilling et al (2003) found that links between changes in women’s positive communication and subsequent distress were no longer significant when controlling for wives’ reported mutual avoidance, suggesting that wives who increased their positive behavior over the course of the workshop may have been avoiding discussion of important problems. Critics of this literature have argued that there are potential statistical and methodological issues (e.g., influential cases and very complex and difficult to interpret models) that cannot be ruled out as explanations for such findings (Stanley et al, 2007). However, if Schilling et al’s (2003) and Baucom et al’s (2006) interpretations of these results are accurate – that some women may have misinterpreted instruction in the PREP workshop to mean that positive communication is good and negative communication is bad regardless of the context of the behavior – these findings may highlight a problem with purely behavioral approaches to relationship distress, as we discuss in more detail below.…”
mentioning
confidence: 99%